UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI DI SMP NEGERI 1 KUBU KABUPATEN ROKAN HILIR - Karsono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on observations conducted at SMP Negeri 1 Kubu, Rokan Hilir, several problems related to teacher performance were identified. These included: (a) the majority of teachers frequently arriving late or being absent without clear reasons; (b) many teachers leaving the school during working hours; and (c) tasks and activities assigned by the principal not being implemented as expected, particularly those scheduled outside official school hours. In addition, many teachers were not adequately prepared with the required learning tools. Remedial and enrichment programs were also not implemented properly, resulting in suboptimal learning processes. This study aimed to improve teacher performance through academic supervision. The research employed school action research (PTS) conducted at SMP Negeri 1 Kubu, Rokan Hilir, with teachers as the research subjects. The study was carried out in February 2015 and involved 20 teachers. The research was based on observations and information indicating that teacher performance was still relatively low. Based on data analysis and discussion, the results showed an improvement in teacher performance. In the first cycle, teacher performance reached 57%, which was categorized as “fairly good.” In the second cycle, teacher performance increased significantly to 80%, categorized as “good.” These findings indicate that supervision activities were effective in improving teacher performance at SMP Negeri 1 Kubu, Rokan Hilir.